Discussing investigational AAV gene therapy with hemophilia patients: A guide. (May 2021) - Sidonio, Robert F.; Pipe, Steven W.; Callaghan, Michael U.; Valentino, Leonard A.; Monahan, Paul E.; Croteau, Stacy E.
Abstract: Gene therapy has the potential to overcome many of the limitations of prophylactic hemophilia therapies. Several clinical trials evaluate investigational adeno-associated virus (AAV)-mediated gene transfer approaches for the treatment of hemophilia A and B. The practical application of these approaches is nuanced by differences in AAV serotypes, transgene modifications, manufacturing, dosing, administration, and approach to follow-up. This guide explores mechanisms of AAV gene transfer, identification of appropriate candidates for clinical trial participation, anticipated trial events that follow infusion of an investigational gene therapy including outcomes to be monitored, and future considerations. Patient-accessible infographic summaries of these topics are included to serve as potential visual aids that healthcare providers may choose to utilize or adapt to guide informed consultation. The fundamentals of AAV-mediated, liver-directed gene transfer for hemophilia are reviewed, to facilitate discussion between healthcare providers, patients, and their families and advocates if considering a trial of investigational gene therapy.